Silver deposited on graphitic carbon nitride prepared under microwave irradiation for photodegradation of 2-chlorophenol. (2022) - Azami, M.S.; Jalil, A.A.; Nawawi, W.I; Mamat, C.R.; Izzudin, N.M.
Abstract: 2-chlorophenol (2-CP) has been extensively utilized in various industries such as agricultural, cosmetic, paper, and biocide. The 2-CP has become a dangerous pollutant that can cause serious water pollution. Photocatalytic degradation is one of the effective destructive methods to remove 2-CP pollutant. Silver deposited on graphitic carbon nitride (Ag/g-C3 N4 ) was prepared using the solid-state method without using any solvent and treated under microwave irradiation. The photocatalysts were characterized using UV–Vis DRS, N2 adsorption–desorption, FTIR, and FESEM analyses. The result shows that the bandgap energy was drastically narrowed after introducing Ag on g-C3 N4 . The deposited Ag on g-C3 N4 provided a high performance (80%) of 2-CP after irradiation for 240 min under visible light. The enhancement of photodegradation was significantly influenced by the well dispersion of the Ag on the surface g-C3 N4 and the low bandgap energy induced the synergistic effect between g-C3 N4 and Ag. The existence of Ag metal on g-C3 N4 prepared under microwave markedly can enhance a great potential photocatalyst for organic pollutants wastewater treatment.